Peer-provided psychological intervention for Syrian refugees: results of a randomised controlled trial on the effectiveness of Problem Management Plus. Issue 1 (8th February 2023) - de Graaff, Anne M; Cuijpers, Pim; Twisk, Jos W R; Kieft, Barbara; Hunaidy, Sam; Elsawy, Mariam; Gorgis, Noer; Bouman, Theo K; Lommen, Miriam J J; Acarturk, Ceren; Bryant, Richard; Burchert, Sebastian; et al.
Abstract : Background: The mental health burden among refugees in high-income countries (HICs) is high, whereas access to mental healthcare can be limited. Objective: To examine the effectiveness of a peer-provided psychological intervention (Problem Management Plus; PM+) in reducing symptoms of common mental disorders (CMDs) among Syrian refugees in the Netherlands. Methods: We conducted a single-blind, randomised controlled trial among adult Syrian refugees recruited in March 2019–December 2021 (No. NTR7552). Individuals with psychological distress (Kessler Psychological Distress Scale (K10) >15) and functional impairment (WHO Disability Assessment Schedule (WHODAS 2.0) >16) were allocated to PM+ in addition to care as usual (PM+/CAU) or CAU only. Participants were reassessed at 1-week and 3-month follow-up. Primary outcome was depression/anxiety combined (Hopkins Symptom Checklist; HSCL-25) at 3-month follow-up. Secondary outcomes included depression (HSCL-25), anxiety (HSCL-25), post-traumatic stress disorder (PTSD) symptoms (PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition; PCL-5), impairment (WHODAS 2.0) and self-identified problems (PSYCHLOPS; Psychological Outcomes Profiles). Primary analysis was intention-to-treat. Findings: Participants (n=206; mean age=37 years, 62% men) were randomised into PM+/CAU (n=103) or CAU (n=103). At 3-month follow-up, PM+/CAU had greater reductions on depression/anxiety relative to CAU (mean difference −0.25; 95% CI −0.385 to −0.122; p=0.0001, Cohen's d =0.41). PM+/CAU also showed greater reductions on depression (p=0.0002, Cohen's d =0.42), anxiety (p=0.001, Cohen's d =0.27), PTSD symptoms (p=0.0005, Cohen's d =0.39) and self-identified problems (p=0.03, Cohen's d =0.26), but not on impairment (p=0.084, Cohen's d =0.21). Conclusions: PM+ effectively reduces symptoms of CMDs among Syrian refugees. A strength was high retention at follow-up. Generalisability is limited by predominantly including refugees with a resident permit. Clinical implications: Peer-provided psychological interventions should be considered for scale-up in HICs.